FAKTOR PENYEBAB OBESITAS PADA REMAJA PUTRI DI ACEH BESAR - Nunung Sri Mulyani; Arnisam Arnisam; Suri Hayatul Fitri; Ardiansyah Ardiansyah (Poltekkes Kemenkes Semarang, 2020)
Background : One of the factors that influence obesity is knowledge, breakfast, fast food consumption, exercise habits.Objective : to find out the factors that cause obesity in young women in Aceh BesarMethod : This research is analytic descriptive with cross sectional approach which was carried out in June 2019 at SMAN 1 Darul Imarah with a sample of 77 people. Obesity is determined by measuring weight and height using a scale and microtoise with the category: obesity if BMI 27. Data collection was carried out using a questionnaire with knowledge variables, fast food consumption, breakfast and exercise habits with data analysis using chi square.Result : The results showed that most teenagers were not obese 41 people (53.2%), good knowledge 49 people (63.6%), fast food consumption was often 40 people (51.9%), breakfast was rare 44 people (57.1 %) and sports habits are rarely 50 people (64.9%).Conclusion : There is a relationship between knowledge, consumption of fast food, breakfast and exercise habits with obesity in young women at SMAN 1 Darul Imarah.